A case of Foix–Chavany–Marie syndrome due to bilateral corona radiata infarcts. Issue 5 (12th May 2019) - Rossi, Fabiana; Oliva, Mariano; Straccia, Giulia; Fratta, Mario; Ugga, Lorenzo; Tedeschi, Enrico; Melone, Mariarosa Anna Beatrice
Abstract: Foix–Chavany–Marie syndrome (FCMS) is a rare type of pseudobulbar palsy characterized by automatic‐voluntary dissociation of movements that depend on V, VII, IX, X, and XII cranial nerves. Most of cases are due to bilateral ischemic lesions of anterior opercula, but the syndrome has also been described after unilateral opercular damage either isolated or associated with contralateral cortico‐nuclear tract involvement. Here, we report the clinical and neuroradiological characteristics of a patient with FCMS due to sequential, bilateral, and symmetrical infarcts of corona radiata, presenting with slurred speech, severe hypophonia, and right central‐type facial palsy that rapidly progressed to inability to speak and swallow. In addition, we observed a sudden onset of neuro‐behavioral changes with psychomotor slowing, aggressive, and oppositive conducts along with emotional lability and involuntary crying. To the best of our knowledge, only one other FCMS case has been previously reported with this peculiar lesional topography.